Liolaemus Chacoensis (Chaco Sand Lizard) : Predation - Rodríguez Muñoz, Melina Jesús (2017)
Liolaemus chacoensis is distributed in the Chaco ecoregion from Paraguay to Argentina (Cei 1993. Reptiles del Noroeste y Este de la Argentina Herpetofauna de las Selvas Subtropicales, Puna y Pampas. Museo Regionale di Scienze Naturali. Torino. 949 pp.). Its biology is poorly known (Fitzgerald et al. 1999. J. Herpetol. 526–535; Pelegrin and Bucher. 2015. J. Nat. Hist. 49:2693–2708; but see the following for reproductive season: Cruz and Ramírez Pinilla 1996. Rev. Esp. Herpetol. 10:33–39). Herein we report an observation of a L. chacoensis being preyed up on by a scorpion.